Challenges for machine learning in clinical translation of big data imaging studies - Dinsdale, NK; Bluemke, E; Sundaresan, V; Jenkinson, M; Smith, SM; Namburete, AIL (Cell Press, 2022)
Combining deep learning image analysis methods and large-scale imaging datasets offers many opportunities to neuroscience imaging and epidemiology. However, despite these opportunities and the success of deep learning when applied to a range of neuroimaging tasks and domains, significant barriers continue to limit the impact of large-scale datasets and analysis tools. Here, we examine the main challenges and the approaches that have been explored to overcome them. We focus on issues relating to data availability, interpretability, evaluation, and logistical challenges and discuss the problems that still need to be tackled to enable the success of “big data” deep learning approaches beyond research.